Concise Synthesis of Multisubstituted Isoquinolines from Pyridines by Regioselective Diels–Alder Reactions of 2‐Silyl‐3, 4‐pyridynes. Issue 49 (13th October 2014) - Ikawa, Takashi; Urata, Hirohito; Fukumoto, Yutaka; Sumii, Yuta; Nishiyama, Tsuyoshi; Akai, Shuji
Abstract A four‐step regioselective synthesis of multisubstituted isoquinoline derivatives from 3‐bromopyridines was developed by the Diels–Alder (DA) reactions of 2‐silyl‐3, 4‐pyridynes with furans, followed by functional‐group transformations. In particular, the silyl group at the C2‐position of the 3, 4‐pyridynes played two important roles: firstly, it functioned as the directing group for the DA reaction, and secondly, it served to introduce diverse substituents at the C1‐position of the isoquinolines by electrophilic ipso‐substitution.